2012
DOI: 10.1037/a0028376
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, gender, and the student athlete.

Abstract: Despite battling perceptions of isolation from the overall college campus, student athletes often report higher social outcomes, such as a greater sense of community, than nonathletes. However, research has also begun to show an intricate networking within these worlds as female student athletes interact more with their peers on campus than do male student athletes, and White student athletes are reporting higher levels of social capital than their African American counterparts. The current study, then, sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 79 publications
0
15
0
5
Order By: Relevance
“…The potential benefits of bonding and cognitive social capital may be more pronounced for women, as these concepts support the importance of women's informal social interactions (Ferlander et al, 2016;Pahl, 2000). A study of US college athletes found that women playing team sports held more social capital than those playing individual sports and men playing team sports (Clopton, 2012). Clopton suggested that women found "communal values" in belonging to a team and that social capital derived from team sports benefited women more than men because of their ability to sustain deeper and more meaningful relationships over time (Clopton, 2012).…”
Section: Social Capital and Sportsmentioning
confidence: 99%
“…The potential benefits of bonding and cognitive social capital may be more pronounced for women, as these concepts support the importance of women's informal social interactions (Ferlander et al, 2016;Pahl, 2000). A study of US college athletes found that women playing team sports held more social capital than those playing individual sports and men playing team sports (Clopton, 2012). Clopton suggested that women found "communal values" in belonging to a team and that social capital derived from team sports benefited women more than men because of their ability to sustain deeper and more meaningful relationships over time (Clopton, 2012).…”
Section: Social Capital and Sportsmentioning
confidence: 99%
“…This means that twenty-five percent of the team is in the same major, therefore many of them are in the same classes (Eitzen 1987). On the other hand, some research shows that athletes display greater levels of academic engagement (Clopton 2012). This highlights all the different points of view on this topic.…”
Section: Athlete Versus Non-athlete and Gpamentioning
confidence: 86%
“…Another reason that women do better than men academically is the fact that female athletes are much less likely to think of themselves as "Jocks" which carries a negative academic connotation while male athletes are at high risk of being perceived that way (Clopton 2012). The concept of a "dumb jock" is a highly gendered stereotype and also a very pervasive concept (Watson 1987;Brede and Camp 1987).…”
Section: Gender and Gpa And Athlete Versus Non-athletementioning
confidence: 99%
See 1 more Smart Citation
“…Despite a lack of causal, but great correlational, evidence of the benefits of sport, numerous stakeholders (i.e., parents, coaches, athletes, sponsors, and fans) proselytize about the positive personal development and social capital benefits of sport. Frequently, they promote and invest in sport as a place to build character (Camiré & Trudel, 2010;Jones & Lavallee, 2009;Erdal, 2018), improve health (Neely & Holt, 2014;Staurowsky et al, 2015;Project Play, 2019), boost academic performance (Broh, 2002;DeMeulenaere, 2010;Staurowsky et al, 2015), and obtain social capital (Clopton, 2012;Dorsch et al, 2015;Erdal, 2018). Some of these benefits are even thought to extend to sport fans-who report higher levels of social capital and a sense of belonging in their communities, compared to others (Wann et al, 2011).…”
Section: Beliefs In the Value Of Sportmentioning
confidence: 99%